دراسة تحليلية للسعة الحرارية المولية عند ثبوت الحجم لمادة كبريتيد القصدير باستخدام نموذج ديباي - عفاف صالح علي الزوالي; سميراء صالح علي شاكونة; حنان الصادق الطاهر عبدالرحمن; انتصار الطاهر سالم الزوالي (Surman Journal of Science and Technology, 2026)
Tin sulfide (SnS) is an important IV-VI semiconductor material with promising applications in thermoelectric materials and solar cells. The objective of this study is to determine the molar heat capacity at constant volume Cv for tin sulfide SnS. This was theoretically investigated using the Debye model, employing the Debye approximation to describe the contribution of lattice vibrations to the heat capacity across a wide range of temperatures. A Debye temperature of 218 K was adopted for this material. Theoretical calculations were performed using MATLAB simulation. The calculated results showed the expected behavior of the molar heat capacity Cv, which is proportional to the cube of the absolute temperature T³ at low temperatures and approaches the classical Dulong-Petit limit at high temperatures. The theoretical Cv results were compared with available experimental results for heat capacity at constant pressure (Cp). The obtained results showed good agreement with published experimental data in the scientific literature, with a relative deviation of approximately 0.34% at 250 K. However, an increasing deviation was observed at low temperatures 13.00% at 100 K and high temperatures 6.50% at 600 K. This indicates that the Debye model provides an excellent approximation in the intermediate range, and the deviations are attributed to a harmonic effect as well as the difference between Cv and Cp. This study provides a reliable analytical framework for estimating the thermal properties of SnS.